Bacteriophage Protects Against Aerococcus viridans Infection in a Murine Mastitis Model - Xi, Hengyu; He, Dali; Li, Dong; Liu, Shan-shan; Wang, Gang; Ji, Yalu; Wang, Xinwu; Wang, Zijing; Bi, Lanting; Zhao, Rihong; Zhang, Hao; Yang, Li; et al. (Frontiers in Veterinary Science, 2020)
Bovine mastitis, an inflammatory disease that occurs frequently in early lactation or the dry period, is primarily caused by bacterial infections. There is growing evidence that Aerococcus viridans (A. viridans) is becoming an important cause of bovine mastitis. The treatment of bovine mastitis is primarily based on antibiotics, which not only leads to a large economic burden but also the development of antibiotic resistance. On the other hand, bacteriophages present a promising alternative treatment strategy. The object of this study was to evaluate the potential of a previously isolated A. viridans phage vB_AviM_AVP (AVP) as an anti-mastitis agent in an experimental A. viridans-induced murine mastitis model. A. viridans N14 was isolated from the milk of clinical bovine mastitis and used to establish a mastitis model in mice. We demonstrated that administration of phage AVP significantly reduced colony formation by A. viridans and alleviated damage to breast tissue. In addition, reduced inflammation was indicated by decreased levels of inflammatory cytokines (TNF-α, IL-1β and IL-6) and myeloperoxidase (MPO) activity in the phage-treated group compared to those in the phosphate buffered saline (PBS)-treated group. To the best of our knowledge, this report is the first to show the potential use of phages as a treatment for A. viridans-induced mastitis.